2015
DOI: 10.1056/nejmra1404726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Physiology of Water Balance

Abstract: T he hypothalamic-neurohypophyseal-renal axis normally maintains water balance during variations in water intake and nonrenal losses of water. Failure of this mechanism is common in hospitalized patients, and it results in a variety of water-balance disorders. In this article, we begin by reviewing the classic, integrative principles of water balance in mammals and then use this classic model as a framework to discuss the genes and gene products (proteins) involved in water balance. In so doing, our goal is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
193
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(203 citation statements)
references
References 77 publications
1
193
0
9
Order By: Relevance
“…1D shows that AQP2 protein was less abundant in kidneys of water-deprived mTUG UBX-Cter mice, when compared with wild-type controls. Renal AQP2 is present exclusively in parts of the nephron where vasopressin regulates the osmotic transport of water to concentrate urine (32). Although other cells contribute material to whole kidney lysates, gross and histologic studies revealed no differences between kidneys of transgenic and wildtype mice (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D shows that AQP2 protein was less abundant in kidneys of water-deprived mTUG UBX-Cter mice, when compared with wild-type controls. Renal AQP2 is present exclusively in parts of the nephron where vasopressin regulates the osmotic transport of water to concentrate urine (32). Although other cells contribute material to whole kidney lysates, gross and histologic studies revealed no differences between kidneys of transgenic and wildtype mice (6).…”
Section: Resultsmentioning
confidence: 99%
“…Vasopressin regulates water permeability in the renal collecting system by both minute-to-minute effects on AQP2 targeting and hour-to-daylong effects on AQP2 abundance (30,32). We considered that the longer-term effects on AQP2 abundance would be most relevant in mTUG UBX-Cter transgenic mice, which are predicted to have chronically accelerated inactivation of circulating vasopressin.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, this normally water-tight membrane becomes water-permeable. Driven by the osmotic gradient of sodium, water is then transcellularly reabsorbed, entering the cells through aquaporin-2 in the apical membrane and leaving the cells for the interstitium through aquaporin-3 and aquaporin-4, which reside in the basolateral membrane (31). In patients with ADPKD, there is a pathologically hyperactive AVP/V2 receptor system.…”
Section: Vasopressin 2 Receptor Antagonistsmentioning
confidence: 99%
“…57 There are four types of AVP receptors, namely, V1a, V1b, V2, and OT, located at different tissues in the body, including the uterus, the pituitary, the kidney, and the cardiovascular system. 58 AVP is also produced in normal human adrenocortical tissue as cells containing AVP were observed in both the adrenal cortex and medulla.…”
Section: Arginine Vasopressinmentioning
confidence: 99%